Developing English for Specific Purposes Instructional Material for Islamic Department Students - Mukhlisin Mukhlisin (STAI Miftahul Ula Nganjuk, 2019)
This study is aimed at developing ( ESP ) English for Specific Purposes Instructional Material for Islamic Department Students . In this case, the product is English for Specific Purposes Instructional Material in teaching English. To support in this study, the appropriate design that the analyst connected research and development ( R & D ). The result of need assessment consists 1) the college need ESP Instructional Material, 2) the students need toward ESP Instructional Material, 3) the Islamic graduates about English at Islamic department, 4) the curriculum maker interview. After that the material mapping to develop the first draft of the material, then gave the product to the expert validation, after revised the result of the tryout of the material, the researcher revised of the product and got the final. The final product consists of the good over, the material by using with the principles of Contextual Teaching and Learning (CTL) and communicative approach which full activities of reading and speaking to improve the learners’ skill also the essential phrases for use the situation in real-life.